Lung microbiome alterations in patients with anti-Jo1 antisynthetase syndrome and interstitial lung disease - Quintero-Puerta, Teresa; Lira-Lucio, Juan Alberto; Falfán-Valencia, Ramcés; Vega-Sánchez, Ángel E.; Márquez-García, Eduardo; Mejía, Mayra; Bautista-Becerril, Brandon; Rojas-Serrano, Jorge; Ramos-Martínez, Espiridión; Buendía-Roldán, Ivette; Pérez-Rubio, Gloria (Frontiers in Cellular and Infection Microbiology, 2023)
Aim To characterize the lung microbiome in the bronchoalveolar lavage fluid (BALF) of patients with Antisynthetase Syndrome (ASSD) according to anti-Jo1 autoantibody positivity and evaluate the correlation with differential cell count and other bacterial genera in BALF. Methods We sequenced the 16S ribosomal RNA gene in the BALF of anti-Jo1-positive (JoP, n=6) and non-Jo1-positive (NJo, n=17) patients, and the differential cell count in BALF was evaluated. The Spearman’s correlation was calculated for the quantitative variables and abundance of bacterial species. Results The Veillonella genus showed a significant decrease (p<0.01) in JoP (2.2%) in comparison to NJo (4.1%) patients. The correlation analysis showed several high (rho ≥ ± 0.7) and significant (p < 0.05) correlations. We analyzed the results obtained for the Veillonella genera and other study variables. The JoP group showed that the abundance of Veillonella had a high negative correlation with macrophages (rho = - 0.77) and a positive correlation with eosinophils (rho = 0.77), lymphocytes (rho = 0.77), and Prevotella (rho = 1). Conclusions The lung microbiome in ASSD patients differs and may affect cell composition, contributing to lung damage mechanisms. The presence of anti-Jo1 autoantibodies showed a low abundance of Veillonella. This genus had a strong and positive correlation with Prevotella abundance and levels of eosinophils and lymphocytes, and it showed a strong negative correlation with the percentage of macrophages.